Perinatal Lethal Gaucher Disease due to RecNcil Recombinant Mutation in the GBA Gene Presenting with Hydrops Fetalis and Severe Congenital Anemia. (9th May 2018) - Bhutada, Ekta; Pyragius, Timothy; Petersen, Scott G.; Niemann, Frans; Matsika, Admire
Abstract : A 35-year-old woman presented at 27-week gestation with hypertension and pedal edema. Antenatal scan showed hydrops fetalis and growth restriction. Cordocentesis showed severe fetal anemia. This was treated with multiple in utero blood transfusions with no clinically significant improvement and intrauterine death occurred at 28 weeks. Perinatal autopsy confirmed severe hydrops with hepatosplenomegaly and visceral effusions. Microscopic examination of the reticuloendothelial organs showed widespread infiltration by large mono- and multinucleate histiocytic cells with fibrillary appearance ("Gaucher cells"). DNA extracted from fetal tissue was submitted for analysis by next generation sequencing which revealed homozygosity for the RecNcil mutation in the GBA gene. Both parents were found to be heterozygous for the variant. The case report highlights a severe form of Gaucher disease with histopathological and molecular confirmation that presents with hydrops fetalis and severe refractory anemia. It also emphasizes the importance of perinatal autopsy coupled with exome sequencing in confirming syndromic diagnosis in the modern area.